Baricitinib Ameliorates Experimental Autoimmune Encephalomyelitis by Modulating the Janus Kinase/Signal Transducer and Activator of Transcription Signaling Pathway - Dang, Chun; Lu, Yaoheng; Chen, Xingyu; Li, Qian (Frontiers in Immunology, 2021)
Experimental autoimmune encephalomyelitis (EAE) is an animal model of multiple sclerosis (MS) and a CD4+ T cell-mediated autoimmune disease. The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway is recognized as the major mechanism that regulates the differentiation and function of T helper (Th) 1 and Th17 cells, which are recognized as pivotal effector cells responsible for the development of EAE. We used baricitinib, a JAK 1/2 inhibitor, to investigate the therapeutic efficacy of inhibiting the JAK/STAT pathway in EAE mice. Our results showed that baricitinib significantly delayed the onset time, decreased the severity of clinical symptoms, shortened the duration of EAE, and alleviated demyelination and immune cell infiltration in the spinal cord. In addition, baricitinib treatment downregulated the proportion of interferon-γ+CD4+ Th1 and interleukin-17+CD4+ Th17 cells, decreased the levels of retinoic acid-related orphan receptor γ t and T-bet mRNA, inhibited lymphocyte proliferation, and decreased the expression of proinflammatory cytokines and chemokines in the spleen of mice with EAE. Furthermore, our results showed the role of baricitinib in suppressing the phosphorylation of STATs 1, 3, and 4 in the spleen of EAE mice. Therefore, our study demonstrates that baricitinib could potentially alleviate inflammation in mice with EAE and may be a promising candidate for treating MS.